INDEPENDENCE CURRICULUM IN PRACTICE: EXAMINING LEARNING MODELS DEPLOYED BY SCHOOL TEACHERS - Nengah Dwi Handayani; Ida Bagus Nyoman Mantra (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2023)
Abstract This study examines learning models applied in learning activities used by teachers in the implementation of the independent curriculum. In this research, a qualitative descriptive method was used. The data were collected through interviews and participant observation in natural classroom settings. This study found that teachers observed in classes with the independent curriculum tended to apply learning models that supported students' creativity and improved their critical thinking skills. There are four learning models that teachers tend to implement, namely Problem-Based Learning (PBL), Project-based Learning (PJBL), Discovery Learning (DL), and Inquiry Learning (IL). These four models can foster 4C skills, namely collaborative, creative, critical thinking or critical thinking, and also communication or building good multi-directional communication in the learning process. This research implies that teachers must be able to choose the right learning model in learning so that students can improve their competence.